Effect of ischemic preconditioning on maximum accumulated oxygen deficit in 400-meter runners - Chen, Y.; Yang, J.; Muradov, O.; Li, X.; Lee, J. K. W.; Qiu, J. (European Journal of Sport Science, 2023)
The main aim of this study was to examine the influence of ischemic preconditioning (IPC) on maximal accumulated oxygen deficit (MAOD). We conducted a three-arm and assessor-blinded randomized, controlled crossover study. Sixteen 400-meter running male athletes (19.9 ± 1.3 years; 1.78 ± 0.05 m; 67.9 ± 5.5 kg) completed three supramaximal intensity tests separated with Control, Local (legs), and Remote (arms) IPC interventions. IPC was induced on the limbs on both sides (4×5 min alternating unilateral occlusion 220 mmHg and reperfusion; arms or thighs; right side first) before participants performed the supramaximal intensity test on a treadmill at 110% VO2max intensity to exhaustion. During each test, indices of respiratory gas exchange, blood lactate, and heart rate were determined. The MAOD was calculated as the difference between the theoretical VO2 demand and the actual VO2 during the supramaximal intensity test. Differences from three trials were analyzed using ANOVA with repeated measures. IPC increased MAOD (RIPC, 59 ± 17 ml/kg/min, p = 0.018; LIPC, 57 ± 15 ml/kg/min, p = 0.037; p < 0.05) compared with Control (49 ± 9 ml/kg/min). Time to exhaustion was enhanced after IPC (Control: 257.2 ± 69.5 s, RIPC, 292.3 ± 66.6 s, p = 0.048; LIPC, 291.6 ± 79.2 s, p = 0.042; p < 0.05). In contrast, the enhancements of RIPC and LIPC trials were similar (p = 1.000). Blood lactate concentrations were similar across the three intervention conditions (p > 0.05). Acute IPC improved MAOD and supramaximal intensity exercise capacity in 400-meter running athletes. The increased MAOD indicated greater anaerobic capacity, which can be the potential mediator for improvement in exhaustion time.